NEGOTIATED ISLAMIC AUTHORITY AND RATIONAL VOTING: Religious Leadership, Voter Typologies, and Local Democracy in Madura - Holilah, Holilah; Marijan, Kacung (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2025)
The enduring influence of Islamic religious authority on local elections raises important questions regarding voter behavior in democratizing Muslim societies. While direct local elections are often associated with the emergence of rational, performance-oriented voting, religious leaders continue to shape electoral outcomes in many regions of Indonesia. Existing studies on Madurese politics predominantly emphasize the consistent and dominant role of kiai and pesantren, yet the interaction between religious authority and rational voting considerations across diverse social groups and geographic contexts remains underexplored. This study addresses this gap through a qualitative case study of local elections in Madura, employing in-depth interviews and participant observation with santri, university students, and community residents across four districts. The findings reveal that Islamic authority continues to influence voting behavior, albeit in a conditional and negotiated manner. Electoral decisions vary across social groups and between rural and urban areas, producing distinct rationales for candidate selection. This article identifies four voter typologies—traditional, rational, critical, and skeptical—and proposes a rationalization process that operates without secularization, indicating that increasing electoral rationality does not necessarily reduce religious authority.